A Statewide Assessment of Electronic Health Record Adoption and Health Information Exchange among Nursing Homes. (21st December 2013) - Abramson, Erika L.; McGinnis, Sandra; Moore, Jean; Kaushal, Rainu; ,
Abstract : Objective: To determine rates of electronic health record (EHR) adoption and health information exchange (HIE) among New York State (NYS) nursing homes. Data Sources/Study Setting: Primary data collected from a novel survey administered between November 2011 and March 2012 to all NYS nursing homes. Study Design: We used a cross‐sectional study design to assess level of EHR implementation, automation of key functionalities, participation in HIE, and barriers to adoption. Data Collection/Extraction Methods: We used descriptive statistics to characterize rates of EHR adoption and participation in HIE and logistic regression to identify nursing home characteristics associated with EHR adoption and HIE. Principal Findings: We received responses from 375 of 632 nursing homes (59.3 percent). Of respondents, almost one in five ( n = 66, 18.0 percent) reported having a fully implemented and operational EHR and a majority ( n = 192, 54.4 percent) reported electronically exchanging information. Nursing homes with 100–159 beds were significantly less likely than other facilities to have implemented or be in the process of implementing an EHR ( p = .011). Conclusions: Our findings present an important systematic look at EHR adoption and HIE by NYS nursing homes. Although the nursing home sector has been reported to lag in health information technology adoption, our results are encouraging. However, they suggest much room for growth and highlight the need for targeted initiatives to achieve more widespread adoption in this important health care sector.